Evaluation of changes in serum lipid profile and fasting blood glucose levels in patients with gall stone disease before and after cholecystectomy - Kumar, Raj; Singh, Vikram; Ahmad, Shabi; Singh, Mayank; Singh, Anshul; Rai, Nandan; Kumar, Shirish; Agarwal, Abhinav; Mittal, Gaurav (International Surgery Journal, 2020)
Background: There is paucity of information regarding the effects of cholecystectomy on serum lipid profile parameters and blood glucose levels in the patients of cholelithiasis. Therefore, this study was undertaken to compare some serum lipid parameters and blood glucose levels in patients of cholelithiasis and effect of cholecystectomy on the same. Methods: The study was conducted on 50 patients of cholelithiasis who were admitted in Surgery department, MLN Medical College over a period of one year and were planned for cholecystectomy. Complete lipid profile (which included total cholesterol, triglycerides, high density lipoproteins (HDL) cholesterol, low density lipoproteins (LDL), very low density lipoproteins (VLDL) and atherogenic index) and fasting blood glucose was evaluated pre-operatively and post-operatively on the 3rd, 7th and further after 1 month of cholecystectomy. Results: Out of 50 patients, maximum of 38% were in their 4th decade with females constituting 82% of total. There was significant elevation in fasting blood glucose and HDL cholesterol on 3rd, 7th and 30th day post-cholecystectomy as compared to pre-operative values (p value<0.0001). Triglyceride and VLDL cholesterol elevated on 3rd and 7th day but it significantly decreased one-month post-cholecystectomy as compared to pre-operative levels (p value<0.0001). However, LDL, total cholesterol and atherogenic index significantly decreased on 3rd ,7th and 30th day post-cholecystectomy. Conclusions: Cholelithiasis is an important cause associated with significant pathological changes in many lipid profile parameters, which will return towards normal after cholecystectomy. This normalization will be a time dependent phenomenon with long term beneficial effects.